1996
DOI: 10.1080/0729436960150205
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Intensive Learning Skills Course for University Students on Restricted Enrolment

Abstract: Prior to the commencement of the 1994 academic year, University of Auckland students who had failed one-half or more of their papers in the previous year were invited to attend a four-day intensive learning skills course conducted by the Student Learning Centre of the University. The course covered various topics such as effective time management and study organisation, preparing for and taking tests and exams, memory and concentration, and writing skills. A total of 74 students attended the course. After fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Finally, Thombs (1995) reported that poor time management was one of the best discriminators for distinguishing between probationary and nonprobationary students. Along with the results of these investigations, our findings support the development of holistic interventions (e.g., Coleman & Freedman, 1996;Manalo et al, 1996;Wlazelek & Coulter, 1999) that address not only traditional study skills, but also time management, procrastination, stress management, and self-monitoring of academic and emotional problems. Our findings also affirm the importance of the time management and personal development components of the CRP curriculum at RIT.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Finally, Thombs (1995) reported that poor time management was one of the best discriminators for distinguishing between probationary and nonprobationary students. Along with the results of these investigations, our findings support the development of holistic interventions (e.g., Coleman & Freedman, 1996;Manalo et al, 1996;Wlazelek & Coulter, 1999) that address not only traditional study skills, but also time management, procrastination, stress management, and self-monitoring of academic and emotional problems. Our findings also affirm the importance of the time management and personal development components of the CRP curriculum at RIT.…”
Section: Discussionsupporting
confidence: 82%
“…An institution may respond to a student's probation by sending the student a notification letter stating the consequences of remaining on probation and identifying campus resources that may enable the student to improve her performance. However, many institutions have developed more intrusive interventions to increase the likelihood that probationary students will return to good standing (see reports of representative programs in Abelman & Molina, 2001;Austin et al, 1997;Coleman & Freedman, 1996;Garnett, 1990;Kirk-Kuwaye & Nishida, 1995;Manalo, Wong-Toi, & Henning, 1996;Ramirez & Evans, 1988;and Wlazelek & Coulter, 1999). "Intrusive" interventions bring students into face-to-face contact with professional or faculty advisors and include instruction and activities designed to improve not only such traditional study skills as note-and test-taking, but also time management, goal setting, help seeking, communication abilities, and so forth.…”
Section: Intervention Programs For Students In Academic Jeopardymentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these studies have considered the effect of individual study skills programmes (Henning & Manalo, 2012;Manalo, Marshall & Fraser, 2009;Manalo, Wong-Toi & Henning, 1996), and the effect of tertiary preparatory courses (Manalo, 2006). This study supplements the 'hard' quantitative evidence that has been produced from these studies and answers the question that Acheson talks of in her paper, i.e.…”
Section: Introductionsupporting
confidence: 57%
“…Intervention strategies such as group intervention (Coleman & Freedman, 1996), individual career advisor/counselor sessions (Glennen, 1976;Hamilton, 1994), study skills courses (Lipsky & Ender, 1990;Manalo, Wong-Toi, & Henning, 1996), money management and goal setting classes (Coleman & Freedman, 1996;Miller & Sonner, 1996), social competence skills building courses (Coleman & Freedman, 1996), and intepersonal problem solving training (Coleman & Freedman, 1996) have been found to be successful. Kirschenbaum and Perri (1982) examined literature on academic competence in adults and concluded that a structured and planned intervention where students perceive themselves as being in control was beneficial to a successful program.…”
Section: Outreach and Intervention Strategiesmentioning
confidence: 99%